Enhanced thermoelectric performance of PEDOT:PSS/PANI–CSA polymer multilayer structures. Issue 9 (8th June 2016) - Lee, Hye Jeong; Anoop, Gopinathan; Lee, Hyeon Jun; Kim, Chingu; Park, Ji-Woong; Choi, Jaeyoo; Kim, Heesuk; Kim, Yong-Jae; Lee, Eunji; Lee, Sang-Gil; Kim, Young-Min; Lee, Joo-Hyoung; et al.
Abstract : A layer-by-layer deposition of two conducting polymers, each layer of which is a few tenths of nanometer thick, has been successfully performed to enhance the thermoelectric power factor of organic thin films. Abstract : A layer-by-layer deposition of two conducting polymers, each layer of which is a few tenths of nanometer thick, has been successfully performed to enhance the thermoelectric power factor of organic thin films, which are critical components of flexible thermoelectric energy harvesting devices. The multilayer films were deposited via multiple solution processes, which exhibit enhanced electrical conductivity without any significant degradation of the Seebeck coefficient, in contrast to a coupling behavior between the electrical conductivity and the Seebeck coefficient in bulk materials. The electrical conductivity and power factor—proportional to the electrical conductivity—of 5(PEDOT:PSS/PANI–CSA) multilayer films are 1.3 and 2 times higher than those of a single PEDOT:PSS layer. Transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) reveal distinct interfaces through which an enhanced electrical conductivity and power factor have been achieved in our multilayer films. From the TEM, EELS, and Raman analyses, a model for the enhancement of the electrical conductivity has been proposed. The enhancement of electrical conductivity occurs via stretching of PEDOT and PANI chains and hole diffusion from the PANI–CSA layer to the PEDOT:PSS layer. The band alignment in the multilayer structure not only enhances electrical conductivity but also maintains the Seebeck coefficient at an optimum value. Our study suggests that the layer-by-layer deposition of polymer thin films is a promising technique for manipulating the thermoelectric properties of each polymer component to enhance thermoelectric performance.